Transportation Development Trends in Reverse Logistics of Fast-Moving Consumer Goods Industries: A Bibliometric Analysis - Fajar Ikhlas, Muhammad; Septiana, Winda; Khairunnisa, Nazihah; Rahardi, Riqqi; Iskandar, Yelita Anggiane; Candra Kurniawan, Adji (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
The city's growing population is causing an increase in traffic demand for supply, mobility, and reverse logistics areas. These are the challenges that participants in the logistics sector are facing, together with rising commodity demand for fundamental requirements. As a result, many scientists are driven to design logistics solutions to mitigate the impact of a growing population, which increases demand for logistics and supply chains, which also has an influence on the community's environment. However, thorough literature survey studies targeted at finding potential treatments for the management of supply chain disorders using bibliometric, network, and theme analyses are still few and limited. According to the findings of the investigation, the primary supply chain themes are provider logistics and reverse logistics. This research has various implications for reverse logistics in the FMCG industry. According to the research, suppliers must understand that implementing environmental activities with their clients may improve their ability to compete in the market, and the "last mile" of distribution may thus be completed by electric cars because the distances are so short that they do not present any difficulties or require elaborate human planning. Therefore, we find that employing logistics providers to manage the FMCG industry or looking at the strategies of logistics providers for renewable energy might be an intriguing future study area.